2011
DOI: 10.2340/00015555-1029
|View full text |Cite
|
Sign up to set email alerts
|

Successful Photopatch Testing with Ketoprofen Using One-Hour Occlusion

Abstract: The standard procedure for photopatch testing includes 24-h occlusion of the allergen, followed by irradiation at 5 J/cm2 ultraviolet A (UVA). Due to the timing, a separate visit to the clinic is needed for UV irradiation. The aim of this study was to determine whether a reduction in occlusion time from 24 h to 1 h, in order to simplify the testing procedure, influences test results when photopatch testing with ketoprofen. A total of 22 patients with a known or suspected photo-allergy to ketoprofen were simult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…This was not the case for those patients who showed lower reactivity. For some contact allergens (in the particular case, a photocontact allergen), for example ketoprofen , a much shorter occlusion time (1 hr) than 48 hrs seems to be as effective as the traditional occlusion period.
…”
Section: Techniquementioning
confidence: 99%
“…This was not the case for those patients who showed lower reactivity. For some contact allergens (in the particular case, a photocontact allergen), for example ketoprofen , a much shorter occlusion time (1 hr) than 48 hrs seems to be as effective as the traditional occlusion period.
…”
Section: Techniquementioning
confidence: 99%
“…The analogues of ketoprofen, piketoprofen and dexketoprofen have a similar behaviour concerning photosensitivity. 61,98 New topical formulations of ketoprofen in plaster aim to reduce UV exposure of the drug, but do not completely hinder this particular side-effect.…”
Section: Targeted Therapiesmentioning
confidence: 99%
“…The ideal variables for each chemical, namely, the ideal exposure time, are not precisely known. Studies with ketoprofen have shown that 1 h of application is enough for skin penetration and induction of positive photopatch tests [10], but no studies have been done with other chemicals.…”
Section: Introductionmentioning
confidence: 99%